Hepatoid adenocarcinoma of the lung mimicking metastatic hepatocellular carcinoma - Yu Miyama (Autopsy and Case Reports, 2020)
Hepatoid adenocarcinoma of the lung is a rare subtype of lung cancer. We report a case of a metastatic hepatoid adenocarcinoma of the lung with aggressive behavior, including biopsy and autopsy findings. The pulmonary tumors showed features indistinguishable from hepatocellular carcinoma and were diffusely positive for Hepatocyte Paraffin 1.